The CB1 cannabinoid receptor antagonist rimonabant chronically prevents the nicotine-induced relapse to alcohol - José Antonio López-Moreno; Gustavo González-Cuevas; Miguel Navarro (Neurobiology of Disease, 2007)
Preclinical and clinical research shows that the cannabinoid brain receptor type 1 (CB1) modulates alcohol- and nicotine-related behaviors. Throughout the nicotine-induced relapse to alcohol, the rats were pre-treated for 10 days with the CB1 cannabinoid receptor antagonist rimonabant (0, 0.03, 0.3 and 3.0 mg/kg i.p.). In this condition, a long-lasting nicotine-induced relapse to alcohol was observed, and this effect was reversed in a dose-dependent manner with rimonabant. Surprisingly, rats that were not exposed to nicotine developed tolerance to the effects of rimonabant from the sixth day. Also, 3.0 mg/kg of rimonabant reduced the responses for sucrose. Evaluation in the Elevated Plus-Maze after nicotine treatment did not reveal anxiogenic effects. Finally, at the conclusion of rimonabant treatment, a rapid reinstatement of alcohol consumption was detected. These results suggest that rimonabant can prevent the relapse to alcohol, even when an interaction with nicotine exists—the most frequent situation in human alcohol abuse.